The real world of democratic theory - Shapiro, Ian. (Princeton : Princeton University Press, 2011)
In this book Ian Shapiro develops and extends arguments that have established him as one of today's leading democratic theorists. Shapiro is hardheaded about the realities of politics and power, and the difficulties of fighting injustice and oppression. Yet he makes a compelling case that democracy's legitimacy depends on pressing it into the service of resisting domination, and that democratic theorists must rise to the occasion of fashioning the necessary tools. That vital agenda motivates the arguments of this book.
Cover; Title Page; Copyright Page; Table of Contents; Preface; INTRODUCTION: Revisiting Democracy's Place; CHAPTER ONE: John Locke's Democratic Theory; CHAPTER TWO: Tyranny and Democracy: Refl ections on Some Recent Literature; CHAPTER THREE: Problems and Prospects for Democratic Settlements: SouthAfrica as a Model for the Middle East and Northern Ireland?; CHAPTER FOUR: Players, Preconditions, and Peace: Why Talks Fail and HowThey Might Succeed; CHAPTER FIVE: Containment and Democratic Cosmopolitanism; CHAPTER SIX: The Political Uses of Public Opinion: Lessons from the EstateTax Repeal.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Democracy; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Democracy; Demokratie; Politisches Denken; Democratie; Politieke theorie; Demokratie